Effect of Adapting to Student Emotions on Servant Leadership of Teachers - Nisha. S. NEDUNGAYIL; Sreedharan. N. V. (Communications of International Proceedings, 2021)
Around the world it’s an ongoing process where, teachers are trying to find new methods to influence and guide the students to achieve their goals. Servant leadership model, can be successfully implemented in teaching through its attribute, student empowerment, which enable teachers to guide students towards their goals. This paper intends to analyse the effect of teacher’s adaptability to student emotions on empowering students. The study, comprised of a sample of 429 college teachers and analysed the effects of gender and experience of teachers in relation to their adaptability to student emotions. The study revealed that, there is no significant influence of these variables, on their adaptability. But the ability of the teachers to adjust to varied student emotions had significant impact on empowering students.
Keywords: Servant leadership; Empowerment; Ability to adapt; student emotions; regression analysis; correlation; Statistical Equation Modelling; ANOVA; F test